Solution for Sustainable Development of Biodiesel Production through Microalgae - Kishor, Kesav; Pandey, Ashutosh Kumar; Singh, Priyanka; Kushwaha, Anita; Rajput, Manish Singh; Singh, Noopur (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 3 No 1&2 (2016): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Energy plays a vital role in global economy. The use of fossils as energy source is increasing day by day, however continuous usage of the fossils is hazardous for the future generations due to the accumulation of greenhouse gases in the environment. So we must curb the use of fossils for the energy and fuel production in order to preserve our ecosystem. Another reason is that being a non-renewable energy source, fossils takes millions of years to renew. To overcome this problem we should use such type of energy sources that are renewable and eco-friendly. Renewable and carbon neutral biodiesel are necessary for environmental and economic sustainability. There is also an alternative way of production of biodiesel by microalgae as provide sufficient energy. Demand of biodiesel is constantly increasing as the reservoir of fossil fuel are depleting. However, the question arises on the viability of first generation biofuel production due to its conflict with food supply. Microalgal diesel production appears to be a viable alternative. As a third generation biofuel, microalgal biodiesel has emerged with an enormous amount of economic and environmental benefits. It has been noticed recently that microalgae is the most favorite feedstock for triacylglycerol (TAG), the storage neutral lipid, for renewable and sustainable biodiesel production, due to their comparable lipid contents, faster growth rates and lesser land requirements in comparison to the non-conventional and non-edible oilseed crops. Many microalgae exceed the productivity of oil of the best producing oil crops. In this article the method applied of biodiesel production has been implemented in such a way to increase its production.